2002
DOI: 10.1210/jcem.87.2.8220
|View full text |Cite
|
Sign up to set email alerts
|

Dermopathy of Graves’ Disease (Pretibial Myxedema): Long-Term Outcome

Abstract: Little is known about the long-term outcome of patients with thyroid dermopathy, an extrathyroidal manifestation of Graves' disease. Also, it is not known to what degree treatment promotes remission of the lesions. The present report supplies information on the natural course of mild, untreated and severe, treated thyroid dermopathy. In this study, we report on the outcomes of 178 patients seen at our institution between January 1969 and November 1995 with thyroid dermopathy who were followed up for an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
86
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 32 publications
1
86
0
10
Order By: Relevance
“…It develops after periods of prolonged standing with dependent edema. In a recent study, Schwartz et al [14] reported 150 patients with TD, 43.3% with non-pitting edema, 27% with plaques, 18.5% with nodules, 2.8% with elephantiastic morphologies, and 8.4% with an unclassified form. In this report, there were five patients with elephantiastic dermopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It develops after periods of prolonged standing with dependent edema. In a recent study, Schwartz et al [14] reported 150 patients with TD, 43.3% with non-pitting edema, 27% with plaques, 18.5% with nodules, 2.8% with elephantiastic morphologies, and 8.4% with an unclassified form. In this report, there were five patients with elephantiastic dermopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion of small lymphatics leads to the accumulation of fluid, swelling, and dermal edema of the affected region. The pretibial area is most commonly involved (99% of the patients with thyroid dermopathy) [14]. In fact, GAG deposition occurs throughout the body without any clinical manifestation [15], but lesions are most often localized in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs most commonly in the lower third of the pretibial region, although it can also involve the feet, toes, knees, upper extremities, or even the face. Ninety percent of patients with PM have hyperthyroidism, and the other 10% may either have hypothyroidism or be euthyroid (1). The pathogenesis of PM is unclear but there appear to be interactions of immunologic, cellular, and mechanical processes (2).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies advocated the external use of glucocorticoids, with the lesion covered with a plastic film to achieve more efficacy (1,(7)(8)(9). There is a recent study reporting a 32-year-old man of PM being treated by subcutaneous injection of triamcinolone acetonide at a large dose (10 mL, 5 mg/mL) monthly (10).…”
mentioning
confidence: 99%